2013
DOI: 10.1016/j.acalib.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Guides Where Students Learn: Do Design Choices and Librarian Behavior Make a Difference?

Abstract: This study investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Contrary to much of the literature, Murphy and Black (2013) challenged the popular assertion that course guides are more useful. They concluded that the value of course guides is discipline-specific.…”
Section: 1mentioning
confidence: 44%
See 2 more Smart Citations
“…Contrary to much of the literature, Murphy and Black (2013) challenged the popular assertion that course guides are more useful. They concluded that the value of course guides is discipline-specific.…”
Section: 1mentioning
confidence: 44%
“…The simplest and most widely-used method for assessing guides and for which data is readily available is the tracking of usage statistics which are generated automatically by the system in which the guide is built (2010: 653). A number of authors have utilised usage statistics to assess their guides (Dalton & Pan 2014;Leighton & May 2013;Murphy & Black 2013;Yeo 2011;Adebonojo 2010;Strutin 2008). However, in instances where statistics are used alone, the assessment is limited in that it does not give any feedback on whether students were able to use the guides or whether they found the guides useful.…”
Section: Guide Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowen (2012) presents the first published instructions documenting how to embed a LibGuide into the BlackBoard learning management system (LMS), paired with a student evaluation of accessing their guide via BlackBoard. Murphy and Black (2013) follow up with their own study of student response to library guides in their LMS. Drawing from CLT, Baker (2014) advocates a need for IL tutorials done via LibGuides.…”
Section: Libguidesmentioning
confidence: 99%
“…(Black 2008;Black and Blankenship 2010;Murphy and Black) To better understand trends in student uptake of library guides embedded within the university's LMS, the transaction logs for the 2009 to 2012 academic years were pulled. These logs provide usage information for each library guide and include the name and number of the course to which the guide was assigned, the library guide name and ID, the date and time for each instance the guide was used, and the email address for the librarian responsible for maintaining the guide.…”
Section: Carmen Library Link: Visualizing Uptake Of Library Guides Emmentioning
confidence: 99%